2018
DOI: 10.18097/pbmc20186405444
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing development of nonalcoholic fatty liver disease and insulin resistance in obesity

Abstract: The factors promoting development of non-alcoholic fatty liver disease in patients with obesity and different state of carbohydrate metabolism have been studied. 43 patients were examined; these included 26 patients with abdominal obesity (BMI=52.9±7.9 kg/m2). The control group consisted of 17 conditionally healthy donors without obesity (BMI=18.9-24.9 kg/m2), seven of them formed a comparison group that was included to compare the results of study on the levels of tissue-specific expression of HSP70 mRNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Tumor necrosis factor (TNF)‐α has been considered a proinflammatory cytokine responsible for eliciting immunopathology in inflammation (S. Li et al., 2016; Vulf et al., 2018); TNF‐α over‐expression has been observed in NAFLD mouse model (Z. Li et al., 2003). By contrast, interleukin (IL)−10 is one of the anti‐inflammatory cytokines that inhibit the production and release of proinflammatory cytokines in inflammatory sites (Maloy & Powrie, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor (TNF)‐α has been considered a proinflammatory cytokine responsible for eliciting immunopathology in inflammation (S. Li et al., 2016; Vulf et al., 2018); TNF‐α over‐expression has been observed in NAFLD mouse model (Z. Li et al., 2003). By contrast, interleukin (IL)−10 is one of the anti‐inflammatory cytokines that inhibit the production and release of proinflammatory cytokines in inflammatory sites (Maloy & Powrie, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α has been considered a proinflammatory cytokine responsible for eliciting immunopathology in inflammation (S. Li et al, 2016;Vulf et al, 2018); TNF-α over-expression has been observed in NAFLD mouse model (Z. Li et al, 2003).…”
Section: Effect Of Cov On Cytokine Expressionmentioning
confidence: 99%
“…In their study on HSP70 expression in various types of cells and tissues of obese patients, Vulf et al established its statistically significant increase in the mononuclear cells of peripheral blood, compared with nonobese individuals. Notably, the expression level of HSP70 was suppressed in visceral subcutaneous adipose tissue and liver, where the authors observed a high expression of proinflammatory cytokines [67].…”
Section: Hsp70 and Hsp72mentioning
confidence: 99%
“…В нашем исследовании маркеры ЭД и провоспалительный IL-6 у пациенток со стеатозом и ожирением в раннем периоде постменопаузы были значимо выше по сравнению с группой контроля. Полученные нами данные согласуются с рядом других исследований, которые изучали цитокиновый статус при НАЖБП [24,25].…”
Section: показатели контроль-бо-м насп-о-м рunclassified